Law, Empire, and the Sultan: Ottoman Imperial Authority and Late Ḥanafī Jurisprudence by Samy A. Ayoub (American Journal of Islam and Society, 2020)
Though their temporal origins, format, and organization betray them as distinctively ‘modern’, the Late Ottoman Mecelle and its commentaries are indebted to a juristic culture that was already by the period in question well over a millennium old. In important ways, their indebtedness to this culture is profound; until recently, however, the degree and nature of this influence had not been properly acknowledged. The monograph under review is a meticulous and formidably-learned study of continuity and change in post-classical Islamic law.To read the full book review, download the PDF file on the right.